Bacterial collagenases – A review. (2nd January 2016) - Duarte, Ana Sofia; Correia, Antonio; Esteves, Ana Cristina
Abstract: Bacterial collagenases are metalloproteinases involved in the degradation of the extracellular matrices of animal cells, due to their ability to digest native collagen. These enzymes are important virulence factors in a variety of pathogenic bacteria. Nonetheless, there is a lack of scientific consensus for a proper and well-defined classification of these enzymes and a vast controversy regarding the correct identification of collagenases. Clostridial collagenases were the first ones to be identified and characterized and are the reference enzymes for comparison of newly discovered collagenolytic enzymes. In this review we present the most recent data regarding bacterial collagenases and overview the functional and structural diversity of bacterial collagenases. An overall picture of the molecular diversity and distribution of these proteins in nature will also be given. Particular aspects of the different proteolytic activities will be contextualized within relevant areas of application, mainly biotechnological processes and therapeutic uses. At last, we will present a new classification guide for bacterial collagenases that will allow the correct and straightforward classification of these enzymes.